Vitamin C in Cardiovascular Disease: From Molecular Mechanisms to Clinical Evidence and Therapeutic Applications - Yichen Xu; Huabo Zheng; Ioana Slabu; Elisa Anamaria Liehn; Mihaela Rusu (Antioxidants)
Vitamin C, also known as ascorbic acid, is an essential nutrient that humans cannot synthesize, making its intake crucial for health. Discovered nearly a century ago, vitamin C is widely recognized for its ability to prevent scurvy and has become one of the most commonly used supplements. Beyond its antioxidant activity, vitamin C is pivotal in regulating lipid metabolism, promoting angiogenesis, enhancing collagen synthesis, modulating remodeling, and stabilizing the extracellular matrix. While preclinical studies have shown promising results, clinical trials have yielded inconsistent findings, due to suboptimal study design, results misinterpretation, and misleading conclusions. This review provides a holistic overview of existing evidence on the pleiotropic role of vitamin C in cardiovascular diseases, identifying both the strengths and limitations of current research and highlighting gaps in understandings in vitamin C’s underlying mechanisms. By integrating molecular insights with clinical data and evaluating the pleiotropic role of vitamin C in cardiovascular disease management and prevention, this review aims to guide future research toward personalized, evidence-based therapeutic strategies in clinical practice.